2018
DOI: 10.1186/s12906-018-2139-3
|View full text |Cite
|
Sign up to set email alerts
|

Anacardic acid inhibits pancreatic cancer cell growth, and potentiates chemotherapeutic effect by Chmp1A - ATM - p53 signaling pathway

Abstract: BackgroundPancreatic cancer is one of the leading causes of cancer related death and its incidence has risen steadily. Although anticancer drugs have been developed based on the new molecular findings, the drugs have produced unsatisfactory results due to toxicity and resistance. Thus, a complementary therapeutic intervention is urgently needed for pancreatic cancer patients.MethodsThe aim of this study was to assess the potential therapeutic effect of Anacardic acid on pancreatic cancer in vitro and elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…In breast cancer cells, AA inhibited cell proliferation by modulating mitochondrial bioenergetics (Radde, Alizadeh‐Rad, Price, Schultz, & Klinge, ). Similar anticancer effects have also been observed in prostate cancer cells (Park et al, ; Tan et al, ). Therefore, AA, a natural compound, may be able to prevent metabolic diseases such as diabetes and cancer.…”
Section: Discussionsupporting
confidence: 74%
“…In breast cancer cells, AA inhibited cell proliferation by modulating mitochondrial bioenergetics (Radde, Alizadeh‐Rad, Price, Schultz, & Klinge, ). Similar anticancer effects have also been observed in prostate cancer cells (Park et al, ; Tan et al, ). Therefore, AA, a natural compound, may be able to prevent metabolic diseases such as diabetes and cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Among these signaling pathways, the p53 signaling pathway has been shown to play a critical role in cancer pathogenesis and treatment (apoptosis) resistance. p53 is therefore an important cellular drug target [65,66] and is also involved in the pathogenic mechanisms of BCa. For example, Zhu et al confirmed that downregulation of the tumor suppressor gene LOC572558 regulates p53 signaling in BCa.…”
Section: Discussionmentioning
confidence: 99%
“…While Momordicinin has been shown to have antioxidant activity, 19 Anacardic acid has been extensively studied and shown to exhibit anticancer activities against breast cancer, 20 prostate cancer, 21 pancreatic cancer, 22 and ovarian cancer 23 . However, the effect of all these compounds on colorectal cells has not, to the best of our knowledge, been published.…”
Section: Resultsmentioning
confidence: 99%